Yang Diingat dari Sejarah Nasional dan International : Fragmen dari Beberapa Ingatan Mahasiswa Baru Fakultas Universitas Indonesia - Eko Aditiya Meinarno (Jurnal Ilmiah Psikologi MIND SET, 2010)
Soekarno, the first president of the Republic Indonesia, once created a jargon called JAS MERAH (literally means red coat) which was the acronym of jangan sekali-kali melupakan sejarah (literally means never forget our history). This jargon is important because history is one of the aspects that build a nation's identity and should be remembered and comprehended by its citizens. This study observes adolescent's recollection about national and international history. Respondents are undergraduate students who respond to questionnaires about their recollection on history. The result is interesting, because the subjects mostly recall politics and war issue and nothing related to humanity and culture. Of eight national heroes recognized by the respondents, only one is unconnected with politics and war. Of eight national historical events, all are related to politics and war. Of twelve world's historical events, nine are linked to politics and war, two are connected with nature and health condition, and only one is related to social issue. Of nine world's heroes which are recognized, all are related to politics and war. These findings are then compared to other similar studies. Although the results are varied, it should be emphasized that participants are quite impressed with political and war-related heroes or events. It is quite likely because politics and war issue get bigger portion in national history than any other subjects, while in the world's history context, the study was conducted when conflict occurred which led to war.